The Effect of Brewing Time on the pH Level and Antioxidant Content of Liberica Coffee Peel and Siam Orange Peel Infusion Tea - Safrina, Rona; Tritisari, Angga (Universitas Tanjungpura, 2024)
Tea is the second most consumed beverage in the world after water. About two-thirds of the world's population consumes tea. The purpose of this research is to determine the pH and antioxidant content of Liberica coffee peel and Siam orange peel infusion tea. The approach taken in this research is quantitative with a factorial completely randomized design (CRD) and two factors. Each was replicated three times. The first factor is the comparison used for coffee peel and orange peel (X), namely coffee peel:orange peel (1:3) (X1), coffee peel:orange peel (1:1) (X2), coffee peel:orange peel (3:1) (X3). The second factor is the brewing time (Y) consisting of three treatment levels: 5 minutes (Y1), 10 minutes (Y2), and 15 minutes (Y3). The results of the analysis of variance (ANOVA) show that the comparison of the composition of Liberica coffee peel-Siam orange peel infusion tea (factor X) can significantly affect antioxidant activity. Additionally, the pH measurement results indicate significant differences in the composition comparison marked by factor X, brewing time (factor Y), and interaction factor (XY). The average pH measurement results in a neutral outcome and affect the stability of antioxidant activity. The conclusion of this research is that chemical analysis of the formula with a composition ratio of 1:1 (X1) with a brewing time of 5 minutes (Y1) has the highest antioxidant content.